An Analysis of the Implementation of Robust Peacekeeping through the Force Intervention Brigade (FIB) in the Congo - Paramitha, Devy Indah; Fadhel Amal, Muhammad (Jurusan Ilmu Hubungan Internasional, 2026)
This research aims to analyze the implementation of robust peacekeeping through the Force Intervention Brigade (FIB) in the Democratic Republic of the Congo in order to achieve sustainable peace. The study applies the concepts of robust peacekeeping and Johan Galtung’s theory of peace. This research is classified as qualitative. The data collection technique used is a literature review, while the data analysis technique follows Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of robust peacekeeping through the FIB has not yet succeeded in fostering positive peace, defined as the absence of structural violence marked by the presence of social justice and equitable distribution of resources. The conflict in the Congo is driven not only by armed groups, but also by social inequality, weak state institutions, competition over natural resources, and the involvement of external actors.